Design procedure to bearing concrete failure in concrete-filled steel tube columns with bolted shear connectors. (1st April 2021) - Ribeiro dos Santos, Lucas; Barreto Caldas, Rodrigo; Figueiredo Grilo, Lucas; Carvalho, Hermes; Hallal Fakury, Ricardo
Highlights: Bolted shear connectors used in concrete-filled composite columns was investigated as load transfer device. Numerical study was carried out with validation already proven in the literature. Experimental and numerical results of the bolted shear connectors were compared with design equations. An analytical formulation of concrete bearing failure was proposed. Abstract: Over the last decades, shear connectors have become indispensable in the engineering of composite structures. However, there is a lack of behaviour of these devices, especially when bolted connectors are used in the load introduction (LI) region of concrete-filled steel tubes (CFST) due to a shortage of specific research. From the perspective of the structural behaviour of these devices, three possible failure modes can occur, namely: bolt shear, steel tube bearing or concrete bearing. In this context, this study aims to clarify the behaviour of bolted shear connectors applied in LI regions subject to concrete bearing failure. The starting point was given by compiling an experimental database of the models available in the literature. After that, using the finite element program ABAQUS, a numerical study was carried out with validation already proven in the literature and, in the next, a parametric analysis was carried out allowing the variation of geometric and mechanical parameters. Finally, an analytical study on the failure of concrete bearing was carried out, resulting in an equation to predict the ultimate strength. Experimental and parametric results were compared with equations presented in the literature and with that proposed in this study. The proposed procedure presented better results when compared with other currently used procedures.